What was Research for the Peasants of Córdoba? Participation in the Early Years of Participatory Action Research - Rappaport,Joanne (2021)
Abstract Reflections on participatory and collaborative research commonly neglect to pay attention to the fact that for community researchers, investigation into their own realities frequently takes forms very different from those of academic scholars. They may use methods that are more explicitly intuitive and may depart from approaches that involve the rigorous collection and systematization of data. This paper explores what research might have meant to the Caribbean peasants of the early 1970s with whom Colombian sociologist Orlando Fals Borda developed his approach to what is today called participatory action research. In particular, it focuses on the field notes of Alfonso Salgado Martínez, a leader of the National Association of Peasant Users-Sincelejo Line (ANUC, Asociación Nacional de Usuarios Campesinos-Línea Sincelejo), juxtaposing them to his published work, both read in comparison to Fals Borda's own notes and writings.